DEVELOPMENT OF CHARACTER VALUES FORWARD (Independent, Active, Honest and Tenacious) AT TARUNA DEVELOPMENT INTENSIVE HIGH SCHOOL, SURABAYA: PENGEMBANGAN NILAI KARAKTER MAJU (Mandiri, Aktif, Jujur, dan Ulet) DI SMA INTENSIF TARUNA PEMBANGUNAN SURABAYA - Dwi Retnani Srinarwati; Muhammad Muhyi; Mimas Ardhianti; Tri Ari Prabowo; I Ketut Samodra; Joko Sutrisno; Ach. Syaifur Rahman (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
Students at the Senior High School (SMA) level are generally faced with conditions that still require assistance from teachers in terms of character education in order to be able to determine appropriate attitudes and behavior according to norms. On this basis, it is inevitable that character education will continue to be strengthened in educational units. The aim of the research is to develop the character of MAJU (Independent, Active, Honest and Tenacious) in the Intensive Cadet Development High School (ITP) Surabaya. The type of research is development research using the ADDIE model. There are five stages of the ADDIE model, namely Analysis, Design, Development, Implementation and Evaluation, which are used to develop the MAJU character. The research subjects were 10 subject teachers at ITP High School, and the research location was ITP High School Surabaya. The research instrument uses observation sheets, data collection techniques using observation and quantitative descriptive data analysis techniques. The results of the research show that the MAJU character (Independent, Active, Honest and Tenacious) can be practiced and implemented by Subject Teachers at SMA ITP Surabaya, with the results of direct observation assessment of subject teachers with an average score of 85 which is interpreted as development the MAJU character is feasible and can be applied at SMA ITP Surabaya. The conclusion from the research results is that MAJU character development at SMA ITP Surabaya can be applied in strengthening the character of students at SMA ITP Surabaya.